FRAZEOLOGY IN DANSKOVĪTE’S PLAYS - Šadurska, Mārīte (Via Latgalica, 2018)
Frequently used phrases in Danskovīte’ plays help to create a typical cultural landscape of Latgale, at the same time a wide range of stylistically expressive vocabulary, most often verbal phrases, and the predominance of poetic comparisons outline the individual writing style of this author. Dramatic work of Danskovīte, which is chosen as the source of phraseology of the research in question, is an area that has not been explored until now. The source of the research consists of 15 plays, 10 of which are available to the readers, “Ontans i Anne” (5 parts), “Sīvasmuotes senču laiki” (3 parts), “Tāva meitas” and “Duorgīs pierkums” (Danskovīte 2008) and five manuscripts of plays: “Lauku kūrorts pilsātnīkim”, “Ontans i rodne”, “Ontans i sābri”, “Ontans i Zīmassvātki” and “Prece ai zatanu”. The aim of the research is to analyse the language of Danskovīte”s plays (phraseology, comparisons, stylistically expressive lexis), revealing the dominant features of the comic. In order to analyse the language of the comic and the features of language as a cultural phenomenon, the linguacultural approach was selected and studies in phraseology were applied. In its turn, the method of receptive aesthetics was used for questionnaires in order to find out the attitude of the respondents towards the plays of Danskovīte, their popularity, as well as to highlight the most characteristic elements of the comic, since, in accordance with the basic principles of receptive aesthetics, text does not have a single meaning – the meaning is formed in the process of interaction between the text and the reader, and a literary work exists as a literary work only in the process of reading and perception and helps to understand that the text is rooted in the communication system and depends on the functioning of the society. For this study, phraseological equivalents in the Latgalian language were searched in “Kalupes izloksnes vārdnīca” (Dictionary of Kalupe vernacular, 1998), in the materials of the Congress of Latgalistics and in the “Latgolys lingvoteritorialo vuordineica” (Latgale lingvoterritorial dictionary, 2012). In the Latvian literary language, however, phraseological equivalents are sought in the Kārlis Mīlenbahs’ and Jānis Endzelīns’ “Latviešu valodas vārdnīcā” (Dictionary of the Latvian language) (1923–1932) and “Latviešu valodas frazeoloģijas vārdnīca” (Dictionary of Latvian phraseology, 2000). In the plays of Danskovīte, about 250 phraseological expressions are excerpted, of which 40% are constructions made by author’s lexical modifications, 31% –traditionally used phraseological units, 23.3% – author’s idioms, 2.4% – author’s semantic modifications, 3.3% – author’s grammatical modifications. It should be noted that 42% of all excerpted units are constructions that include comparisons, where the most part includes a component that identifies a feature from the world of animals, often ascribing animal conduct and properties to a person. Authors’ idioms are used occasionally, functioning only in literary works of the given writer, and they do not have equivalents in the phraseology of the Latvian or other languages. The study of modifications of phraseological units is important in view of the fact that such idioms in the plays of Danskovīte make up about 70% of the total number of all types of set phrases in general; only 30 phraseological units exist in a standardized form, thus most of the existing set phrases in Danskovīte’s plays form the transformations of prescriptive phraseology of all kinds – grammatical, lexical and semantical. The number of modifications includes author’s own phraseology – idioms, which determine the formation of the phraseological expression and specific style of writing. Conceptually, prescriptive phraseological units are understood in terms of stable and traditionally established word combinations, the common meaning of which is different from the meaning of individual components of the phrase. The main methods of creating comic effect in terms of prescriptive phraseology are mostly comparisons, for example, kuo cītumnīks (like a prisoner), kuo bomzs (like a beggar), kuo iz pasyutiejuma (by order), kuo diele (like a leech), kuo myusa (like a fly), kuo troks (like mad). There are also other methods at the basis of the phraseology of Danskovīte’s plays, but it is difficult to find a common characteristics, since their differences are nuanced and context specific. Viewing the lexical modifications by keyword, it is obvious that combinations with the components of tongue, head and eye are represented most often. The second type of transformations consists of phraseological units, which change the grammatical features in author’s language. As already mentioned, they are fewer in number. One of the characteristics of the grammatical modifications is the addition of prefixes that deny the activity specific to the object or subject, or, on the contrary, reinforce such activity, for example, like in the phraseological unit borrowed from Russian: наступить на хвост > iz astes (na)izkuopt. Semantic variations change the meaning of phraseological units, although any modification more or less strongly promotes the departure of the idiom from its main meaning registered in dictionaries, however, this modification is more pronounced in terms of the change of meaning. Analysed in this study are the semantic modifications of phraseological units: kuo syvāns (like a piglet) and kuo bārns (like a child). Danskovīte applies several ways of creating comic effect: misapprehension and comic action and behaviour revealed in a grotesque manner; exaggeration and comic language, peculiarities of pronunciation, associations, epitomized language and misunderstandings.